The Effect of Banking Competition and Efficiency on Banking Performance Moderated by GCG and Crisis Factors - Indah Tri Forniawati; Sudiyatno, Bambang (SENTRALISASI, 2024)
The aim of this research is to test the influence of the level of competition on bank profitability, bank efficiency on bank profitability, test the relationship between competition and bank efficiency and company performance using ROA as a measure of performance, while GCG and the crisis period due to the pandemic are used as moderating variables for this relationship. . Testing of this research uses the multiple regression analysis method with the help of the SPSS version 21 program. The results of this research show that competition is a variable that has a positive and significant influence on banking performance. The greater competitive ability of banks will improve their performance. However, the bank's technical efficiency has not shown significant results. The moderating effect of implementing GCG by banks does not seem to be able to improve the relationship between competition and performance. The same results were also obtained on the relationship between bank efficiency and performance which also cannot be moderated by GCG. The moderating effect of the crisis period was found to be significant on the relationship between competition and bank performance, whereas during the crisis the relationship between competition and bank performance remained low. However, bank efficiency was not moderated by the crisis period resulting from the pandemic.